Role of nutrition in cerebral palsy treatment - comprehensive literature review - Iwona Welian; Michał Leśniewski; Karolina Maliszewska; Izabela Oleksak; Joanna Ziółkowska; Bartosz Mazur; Karolina Gendek; Mikołaj Smach; Magdalena Mazur; Wiktoria Wilanowska (Kazimierz Wielki University, 2024)
Introduction and purpose: A collection of symptoms known as cerebral palsy first manifest in early childhood and result in profound physical impairment. Cerebral palsy is thought to affect 1 in 500 live births, or roughly 17 million people worldwide. The type of cerebral palsy determines the clinical symptoms. Movement coordination disorders, epilepsy, muscle weakness, and feeding difficulties are the most common symptoms. The purpose of this article is to familiarize readers with the options for nutritional therapy for cerebral palsy patients. Material and methods The following review was based on articles from the PubMed and Google Scholar databases. Key search terms included cerebral palsy; nutrition; treatment; gut microbiota.. State of knowledge Early identification of malnutrition symptoms and appropriate interventions, such as the implantation of a percutaneous endoscopic gastrostomy tube in patients who are unable to swallow food, are the cornerstones of nutritional therapy for cerebral palsy patients. Dysphagia is a major problem in the population of patients with cerebral palsy, and multidisciplinary therapy is necessary for them. Patients' serum vitamin D levels are also influenced by their diet; 50% of those with cerebral palsy have a deficiency in this nutrient. Conclusions For people with cerebral palsy, nutrition is very important. Premature death may arise from malnutrition brought on by the disease's advancement. As a result, individuals with cerebral palsy need to receive specialized care